Mandakini Kund behind the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The temple complex features a tranquil reservoir, known as the Mandakini kund (water tank), positioned behind the Mahakal Temple and in the left front of the Undeshwar Temple. Alongside the three temples within the complex, the Mandakini Kund is safeguarded as a protected monument under the jurisdiction of the Jaipur Circle of the Archaeological Survey of India (ASI). Serving as a sacred water body within the Bijolia temple compound, the Mandakini Kund is a site where devotees frequently engage in ceremonial bathing rituals.